The effect of demographic characteristics, Country of birth and country of medical training on the peer evaluations of internal medicine resident physicians - G.D. Everett; L. Albadin; Y. Du (Greater Baltimore Medical Center, 2019)
Background: Peer review by resident physicians, a standard evaluation technique, has rarely been studied for potential biases related to demographic and cultural characteristics of trainees. Objective: The study sought to determine whether peer evaluations were favorably biased toward trainees of similar background. Methods: This observational study was conducted in the Internal Medicine residency of a large, metropolitan, community hospital, and included all 91 Internal Medicine residents who had entered the program from 1 July 2009 thru 30 June 2017. Of 3,445 Peer Evaluation Forms (PEF)s offered, 2,922 (84%) were completed and studied. Multivariate statistical analysis was completed. The primary dependent variable was the Peer Evaluation Score (PES). Independent variables included age, gender, race, birth country and country of medical school training. Confounding variables included United States Medical Licensing Examination (USMLE) and In-Training Examination (ITE) scores, and the American Board of Internal Medicine (ABIM) yearly assessment. Results: Confounding factors accounted for most of the variation. Among the independent variables, only age difference and medical school country were statistically associated with PES. Race and Gender were not significant. Conclusions: Peer evaluations were not significantly biased by race or gender similarities and only minimally biased by age and medical school country similarities.